EKSPLORASI GUNUNG ES DAN PROSES “U” SEBAGAI SEBUAH METODE PEMBELAJARAN DALAM PELATIHAN PENGUATAN MODERASI BERAGAMA - Fauzan, Mohamad; Restendi, Dedi (Balai Diklat Keagamaan Bandung, 2024)
This study aims to assess the effectiveness of the Iceberg Analysis and U-Process methods in training programs designed to strengthen religious moderation, using the Kirkpatrick model to evaluate reaction and learning levels. A survey and descriptive analysis were employed to measure training effectiveness. The study involved a population of 90 participants, with a sample size of 73 determined using the Morgan and Krejcie sample formula. The instrument's validity and reliability were tested, and a Paired Sample T-Test was used to analyze learning outcomes. Descriptive analysis was conducted based on the Iceberg Analysis and U-Process learning models. The findings indicate that the training evaluation at the reaction level falls into the